The Effectiveness of Presidential Democratic System Government in Multiparty Systems - Oktaviani, Annisabella; Prasetyoningsih , Nanik (Universitas Muhammadiyah Yogyakarta, 2024)
Applying a presidential democratic system to a multiparty system has become a fascinating and controversial topic in recent years. Several countries, including Indonesia, have implemented a presidential system accompanied by a multiparty system to improve the quality of democracy and government stability. This research examines the effectiveness of implementing a presidential democratic system in a multiparty system, focusing on government stability and implications for effectiveness. Using normative juridical legal research methods shows that implementing a multiparty system in a presidential government system weakens the presidential system and has implications for executive and legislative relations. Three things have repercussions: first, the many interests of political parties that conflict with government policy; second, the absence of a permanent coalition arrangement; and third, the weakness of the President's position. Ideally, implementing a multiparty system, stability, and effectiveness of government requires extra balance, firm government, and authority in developing the government system. It can be concluded that implementing a presidential democratic system in a multiparty system has several significant implications for the stability and effectiveness of government.